Systematic Review of the Relationship Between Cultural Religiosity, Emotion Regulation, and Rumination Within the Framework of Educational Psychology - Azadi , Zohreh; Rashidizadeh , Zeynab; Elahi, Mohammad (Mental Health and Lifestyle Journal, 2025)
The aim of this systematic review was to examine the relationship between cultural religiosity, emotion regulation, and rumination within the framework of educational psychology. Given the significant role of emotional and cognitive processes in individual development and education, understanding how components of religiosity within the Iranian cultural context influence these constructs is of particular importance. A systematic search was conducted in both national and international databases, including Google Scholar, Scopus, PubMed, Noormags, SID, and Magiran, using relevant keywords. Studies published between 2000 and 2025 that examined the relationship between religiosity, emotion regulation, and rumination were included in the review. The findings indicated that cultural religiosity is generally associated with increased use of adaptive emotion regulation strategies and reduced rumination. Components such as meaning-making, religion-based social support, a sense of connection to a transcendent source, and acceptance were identified as important mechanisms through which religiosity influences emotion regulation. The results also demonstrated that religiosity, through strengthening positive emotion-focused strategies, may reduce maladaptive cognitive processes such as rumination. Nevertheless, several studies emphasized the dual role of religiosity and showed that unhealthy or compulsive forms of religiosity may be associated with increased anxiety and repetitive thoughts. Overall, the evidence from the present review suggests that cultural religiosity, within the socio-cultural context of Iran, can function as a protective factor against negative emotions and rumination and, through improving emotion regulation, may contribute to the enhancement of educational processes and psychological development.